Productisation business model in non-OEM aero-engine MRO service providers - Tjahjono, Benny; Tomiyama, Tetsuo (IOS Press, 2016)
The combination of product and service to provide customer’s satisfaction has been known since 1990s in the aerospace industry, particularly within MRO (Maintenance-Repair-Overhaul) service providers. Initially, the OEMs offered servitisation solutions by bundling the product with services. However, to remain competitive, the non-OEM MRO service providers also initiated bundling its service with products as offerings. This productisation business model is a reverse approach of a servitisation business model. This paper identifies and proposes five types of the productisation business model and each of these types will be shown with a descriptive analysis and illustrations to highlight the understanding of the evolution towards providing offers by bundling services with products. Through this study, non-OEM aero-engine MRO service providers will be able to assess the most suitable business model, based on the MRO service provider’s strengths and challenges.
Keywords: productisation; business model; MRO Service Provider